The selectivity of drugs blocking ganglionic transmission in the rat - Quilliam, J. P. (1964)
By comparing the effects on ganglionic transmission and on the pre- and post-ganglionic nerves in the isolated superior cervical ganglion preparation of the rat, the selectivity of several drugs was assessed quantitatively. Hexamethonium, tetraethylammonium, nicotine and tubocurarine blocked transmission in concentrations which did not affect nervous conduction and were considered to be highly selective in action. Atropine, amylobarbitone and paraldehyde depressed nervous conduction appreciably in ganglion-blocking doses, but not enough to account wholly for the block in transmission and they were therefore considered as being moderately selective. The ganglion blocking actions of mephenesin, procaine, methylpentynol, methylpentynol carbamate and benactyzine were nonspecific, showing general depression of neuronal activity. Ganglion block with bretylium was nonselective in its site of depression of the postganglionic neurone in concentrations which only partly depressed the preganglionic nerve.